2015
DOI: 10.1002/btpr.2200
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of uricase production under uncertainty: Contrast of chromatographic purification and aqueous two-phase extraction (with and without PEG recycle)

Abstract: Uricase is the enzyme responsible for the breakdown of uric acid, the key molecule leading to gout in humans, into allantoin, but it is absent in humans. It has been produced as a PEGylated pharmaceutical where the purification is performed through three sequential chromatographic columns. More recently an aqueous two‐phase system (ATPS) was reported that could recover Uricase with high yield and purity. Although the use of ATPS can decrease cost and time, it also generates a large amount of waste. The ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…One of the major constraints of large‐scale ATPS is the processing to remove phase components, which are considered contaminants. It was previously demonstrated that UF/DF can hinder the potential use of an industrial‐sized ATPS because the high turnover of membrane filters required for this unit operation, which contributes to high production costs . This needs to be evaluated, but the present work analyzed the increase in sample input, therefore requiring a reduced system which could become insensitive to the costs of phase removal operations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major constraints of large‐scale ATPS is the processing to remove phase components, which are considered contaminants. It was previously demonstrated that UF/DF can hinder the potential use of an industrial‐sized ATPS because the high turnover of membrane filters required for this unit operation, which contributes to high production costs . This needs to be evaluated, but the present work analyzed the increase in sample input, therefore requiring a reduced system which could become insensitive to the costs of phase removal operations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, modeling techniques, like Monte Carlo simulation, can be incorporated to mimic real‐life variation and understand their impact on production costs. Examples of successful application of these tools include comparisons between different types of equipment or operating strategies, optimization of different operation parameters, evaluation of different purification strategies, analysis of different strategies for developing autologous cell therapies, and analysis of pilot‐scale production of protein‐based pigments …”
Section: Introductionmentioning
confidence: 99%
“…To create the variations analyzed in the worst and best‐case scenarios, published or experimental data can be used. For the variation in materials costs, a range of ±25% was used as reported before, while labor wages were varied ±10%. Production titer range used was 7.95 × 10 14 ± 4.95 × 10 13 UFP/L, these values consist of the mean plus and minus three standard deviations, in order to cover above 99% of possible values.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The impact of improvement on process parameters at large scale production of recombinant proteins using ATPS were analyzed and compared to the recovery of pharmaceutical‐grade uricase through chromatography. It was found that ATPS provided a lower production cost for production of uricase, moreover, the incorporation of recycling of phase forming chemicals does not increase production costs significantly.…”
Section: Strategies To Maximize Large‐scale Atps Incorporationmentioning
confidence: 99%
“…From an economic perspective, recycling of ATPS components has been evaluated through bioprocess modeling . For the recovery of recombinant uricase, a model has been constructed with and without phase recycling .…”
Section: Potential Trends and Current Challengesmentioning
confidence: 99%